2012
DOI: 10.1074/jbc.m112.363044
|View full text |Cite
|
Sign up to set email alerts
|

Essential Functions of C Terminus of Drosophila Topoisomerase IIIα in Double Holliday Junction Dissolution

Abstract: Background: Topoisomerase III␣ (Top3␣) and Blm dissolve Holliday junctions into non-crossover products. Results: The Top3␣ C terminus binds to Blm and DNA substrates and is important in vivo. Conclusion: The C-terminal domain of Top3␣ is required for dissolution and cellular functions. Significance: The Top3␣ C terminus is an essential component of the dissolvasome complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Interestingly, the fruit fly Drosophila melanogaster possesses neither a RMI1 nor RMI2 ortholog. Thus, dHJ dissolution in that organism may be mediated by the Blm-Topo III␣ complex (8,31). Consistent with this premise, it has been shown that RPA enhances dHJ dissolution catalyzed by the D. melanogaster Blm-Topo III␣ pair.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, the fruit fly Drosophila melanogaster possesses neither a RMI1 nor RMI2 ortholog. Thus, dHJ dissolution in that organism may be mediated by the Blm-Topo III␣ complex (8,31). Consistent with this premise, it has been shown that RPA enhances dHJ dissolution catalyzed by the D. melanogaster Blm-Topo III␣ pair.…”
Section: Discussionsupporting
confidence: 64%
“…In this multienzyme complex, the activities of the RecQ helicase and TOP3 coordinate with each other to catalyze the dissolution of double Holliday junctions, which proceeds by the migration of the junctions towards each other until they merge to form a hemi-catenated structure that is processed by TOP3 (86). In addition to its role during the unlinking of this hemicatenane, TOP3 also assists the convergent branch migration reaction primarily driven by the ATP-dependent helicase activity of Rqh1/Sgs1/BLM (87)(88)(89). The mechanism by which TOP3 manipulates DNA topology during the convergent branch migration is still not clear, although it seems likely that the activity of the RecQ helicase specifically enables TOP3 to efficiently release the torsional stress associated with convergent branch migration (90).…”
Section: Synergy With Other Enzymesmentioning
confidence: 99%
“…Finally, rmi1 is epistatic to top3, and the slow growth phenotype of Drmi1 strains can be suppressed by mutations in the SGS1 gene (Chang et al 2005;Mullen et al 2005). Rmi1 is a conserved protein, being present in nearly all eukaryotes although no ortholog has been found in D. melanogaster (Yin et al 2005;Chen et al 2012). As with TopoIIIa, Rmi1 homologs are essential in S. pombe, A. thaliana, and mice (Chang et al 2005;Hartung et al 2008;Chen et al 2011;Guiraldelli et al 2013).…”
Section: Dissolution Of Double Holliday Junctionsmentioning
confidence: 99%